Prototype System to Anticipate Disruption of the IoT-Based Salted Fish Drying Process - Dasmen, Rahmat Novrianda; Haq, Ainan Dinul (Program Studi Teknik Elektro Universitas Khairun, 2023)
As a country that has many islands, our country also has a lot of sea qhich means it also produces a lot of fish, but fish quickly rot if left alone without a preservation process. One of the preservation process.One of the preservation processes can be by drying in the sun, but erratic weather can make it difficult for fishermen in the preservation process, therefore a system is made that can detect rain and disturbances such as cats by using a PIR sensor with an automatic control system when it rains or distrubnaces. It will move the dryng into a room that has prepared a heating lamp as a temporary substitute for sunlight. Based on the test results, the LDR and Raindrop sensors successfully read the weather data as given and the system can respond to the data provided by the sensor, Based on the test results, the PIR sensor can read the approaching movement in the dryer area and the safety system is directly active. Based on the results of testing the telegram notification that has been carried out, it was found that there was one failure to be sent out of five attempts. The average photo submission time is 2 seconds